How donor behaviour is influenced by Social Media - Take Taiwan Fund for Children and Families on Facebook as an example. - WU, PEI YU (2017)
Non-profit organizations rely on the donation from their donor's financial support so that they could complete their mission to the society. However, while the non-profit fundraising marketing environment has become more and more competitive, the charity has conducted and planned multiple marketing strategies beyond the booming social media platform. It is not only because the social media platform has been widely used in people's daily life but also be seen as a new way for brand to communicate or deliver message to their consumers. Non-profit organization in Taiwan also enhanced their management on social media with their donors in recent year, especially on the Facebook fan page.